Leveraging Opportunities and Challenges in Integrating AI Technology into Traditional Learning Methods in Parepare - Rahman, Ali; Aniati (LPPM Undiksha, 2025)
In an increasingly digital era, the integration of artificial intelligence (AI) in education has become a pressing challenge. The main issues faced are the gap in technological infrastructure, especially in remote areas, and resistance among educators to adopt new technologies. This study aims to explore the opportunities and challenges of implementing AI in traditional learning methods. The research method used is a mixed approach, including quantitative research through surveys and qualitative research. The study population consisted of 5000 students, teachers, and parents, with a sample of 750 people taken using stratified sampling techniques. Data collection was carried out through questionnaires and in-depth interviews. Data were analyzed using SPSS statistical software Version 29.0 for quantitative analysis and thematic analysis for the qualitative part. The results of the study indicate that AI can improve learning personalization and administrative efficiency, but major challenges in terms of infrastructure and data ethics remain. Conclusion, the importance of collaboration between government, educational institutions, and technology to create an innovative and sustainable education ecosystem. Implications of effective training programs for educators in integrating AI in education optimally. The implications of this study indicate that the integration of artificial intelligence (AI) technology in traditional education systems can bring significant changes to the quality of learning.